Ethiopian Agriculture: A dynamic geographic perspective - Chamberlin, Jordan; Schmidt, Emily (University of Pennsylvania Press, 2012)
The opportunities and constraints facing Ethiopian agriculture are strongly influenced by geographical location. Ethiopia’s diverse landscape defines certain agricultural production potentials, access to input and output markets, and local population densities, which determine both labor availability and local demand for food. Understanding the geographical expression of Ethiopia’s agricultural and rural development options provides greater information for more locally targeted policy options.